Potassium Sorbate Induces Oxidative Stress and Genotoxicity in Human Lymphocytes - Malinee Pongsavee; Rajnikant Mishra (Indian Journal of Forensic Medicine & Toxicology, 2021)
Potassium sorbate, a potassium salt of sorbic acid, has been used as food preservative and antimicrobial agent.Some observations in rat and hamster cells suggest its toxicity. However, observations in human cells arelimiting. Therefore, it has been intended to investigate impacts of potassium sorbate on human lymphocytes.The lymphocytes were cultured and treated with 0.5, 1.0, 1.5 and 2.0 mg/ml of potassium sorbate for 24 and48 h. Evaluations of its impacts were done through the MTT assay, analysis of chromosomal aberrations,formation of micronucleus and activities of superoxide dismutase. The results revealed that potassiumsorbate induced oxidative stress, genotoxicity, damages to chromosome, formation of micronucleus inhuman lymphocytes.